Inelastic neutron scattering investigation of the crystal field excitations of NdCo5 - Passos, FDA; Nilsen, GJ; Patrick, CE; Le, MD; Balakrishnan, G; Kumar, S; Thamizhavel, A; Cornejo, DR; Jiménez, JL (American Physical Society, 2023)
We present an inelastic neutron scattering study of the crystal electric field (CEF) levels in the intermetallic ferrimagnets RECo5 (RE=Nd and Y). In NdCo5, measurements at 5K reveal two levels at approximately 28.9 and 52.9 meV. Crystal-field calculations including the exchange field Bexc from the Co sites account for both of these, as well as the spectrum at temperatures above the spin-reorientation transition at ∼280 K. In particular, it is found that both a large hexagonal crystal field parameter A66(r6) and Bexc are required to reproduce the data, with the latter having a much larger value than that deduced from previous computational and experimental studies. Our study sheds light on the delicate interplay of terms in the rare-earth Hamiltonian of RECo5 systems, and is therefore expected to stimulate further experimental and computational work on the broader family of rare-earth permanent magnets.